Psychometric evaluation of the Russian version of the flourishing scale in a sample of older adults living in Siberia; Health and Quality of Life Outcomes; Vol. 17 - Didino D. Daniel; Taran Е. А. Ekaterina Aleksandrovna; Barysheva G. A. Galina Anzelmovna; Casati F. Fabio (2019, 2019)
Title screen